Examination of The Mental Health Componet of Quality of Life of Hemodialysis Patients and Its Relationship to Perceived Expressed Emotion, Coping Self Efficacy, Optimism, Self Esteem, and Social Support - Özden YALÇINKAYA ALKAR; A. Nuray KARANCI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: This study aimed to examine the mental health component of quality of life (MHC) of Hemodialysis patients and its relationship with personal characteristics and other resources within the Conservation of Resources (COR) model. Method: Demographic variables and Hemodialysis related information of patients, with the other resources classified as resources according to COR model, were also included in the study. One hundred and six Hemodialysis patients voluntarily participated in the study. For the study, perceived expressed emotion, optimism, self-esteem, perceived social support and perceived coping self efficacy were taken as resources and were also included as measures. After examining the correlational matrix among the variables of, in order to examine variables related to MHC and test the main hypothesis of the study, multiple regression analysis was conducted. Results: The results of the analysis showed that age, income, house ownerhip, presence of additional diagnosis, self esteem, perceived criticism/hostility and coping self efficacy were significantly related to MHC. Directions of the relationship between age, presence of additional diagnosis, and criticism/hostility were negative with the outcome variables, whereas, directions of the relationship between income, house ownerhip, self-esteem and coping self-efficacy were positive with the outcome variable, MHC. Conclusion: Patients’ concerns about various aspects of demographic and illness related variables, perceived coping selfefficacy, self-esteem, and criticism-hostility were found to be predictive of their MHC.